2021
DOI: 10.1073/pnas.2106556118
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in tRNA modifications and abundance during T cell activation

Abstract: The tRNA pool determines the efficiency, throughput, and accuracy of translation. Previous studies have identified dynamic changes in the tRNA (transfer RNA) supply and mRNA (messenger RNA) demand during cancerous proliferation. Yet dynamic changes may also occur during physiologically normal proliferation, and these are less well characterized. We examined the tRNA and mRNA pools of T cells during their vigorous proliferation and differentiation upon triggering their antigen receptor. We observed a global sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…We further examined and quantified the change in tRNA modifications during HCMV infection based on tRNA sequencing and the effects of modifications on the obtained sequence, as described by Rak et al, 2021. We found that the level of most of the modifications does not change between uninfected and late-infected samples (Figure 2A, r=0.95, p<0.001).…”
Section: Resultsmentioning
confidence: 98%
“…We further examined and quantified the change in tRNA modifications during HCMV infection based on tRNA sequencing and the effects of modifications on the obtained sequence, as described by Rak et al, 2021. We found that the level of most of the modifications does not change between uninfected and late-infected samples (Figure 2A, r=0.95, p<0.001).…”
Section: Resultsmentioning
confidence: 98%
“…using LC–MS/MS techniques ( Supplementary Table S3 ) ( 9–11 , 13–15 , 65 , 66 ). Recent studies using HTS techniques have identified specific tRNA modifications in human and mouse cells that are significantly altered under pathogenic infection ( 67 , 68 ) and during T cell activation ( 32 ). This evidence implies that dynamic changes in tRNA modifications may be a general response of cells to stress conditions; however, the modifications that can be detected by LC–MS/MS methods cannot clarify the specific tRNA isotypes, and the data obtained from HTS are currently far from sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…The level of tRNA modification is altered during T-cell activation. It has been found that yW and ms 2 t 6 A modifications are significantly reduced during T cell proliferation, which may be to reduce the occurrence of ribosomal frameshifting and improve translational fidelity [79]. A recent study revealed that TRMT61A-mediated m 1 A modification of the tRNA 58 promotes the translation of multiple key proteins such as MYC by modulating codon decoding, to ensure a rapid immune response in CD4 + T cells (Figure 3B).…”
Section: Trna Modifications and Immunitymentioning
confidence: 95%